2015
DOI: 10.1155/2015/145154
|View full text |Cite
|
Sign up to set email alerts
|

Healing Relationships: A Qualitative Study of Healers and Their Clients in Germany

Abstract: Background. The aim of this study was to investigate the nature of the relationships between healers and their clients in Germany. Methods. An interdisciplinary research team performed semistructured interviews with healers and clients and participatory observation of healing sessions. All interviews were digitally recorded, transcribed, and analyzed using content analysis. Results. Fifteen healers and sixteen clients were included. The healer-client relationship was described as a profound and unique experie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
(43 reference statements)
1
13
0
1
Order By: Relevance
“…This required intention to heal, and then relinquishing all intention. 15,39 Some healers see this as the main mechanism through which they effect change. 40 Consequently, clients were enabled to take control, in what has been described as a self-healing capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This required intention to heal, and then relinquishing all intention. 15,39 Some healers see this as the main mechanism through which they effect change. 40 Consequently, clients were enabled to take control, in what has been described as a self-healing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, healers have been characterised as teachers, 27 companions or coaches 39 on the client's healing journey, with clients as active agents 16 who should share authority. 32 This differs from psychotherapeutic accounts of quantum change, in which people report being passive recipients, experiencing change without particular effort or intention.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Anthropological research highlights the therapeutic impact of the relationship between healers and healees. 33 , 34 Healing is an innate capability, a natural process; therefore, the healing relationship is facilitative.…”
Section: Antecedents Of Healingmentioning
confidence: 99%
“…Transcendent experiences have been defined and explored in depth by Levin and Steele who reported that while they are difficult to characterise, they typically involve a state of altered consciousness and a sense that there is more to reality than is evident within the usual everyday boundaries (Levin & Steele, 2005), such as a divine presence beyond physical experience. For Stöckigt, a transcendent experience is one which lifts a person beyond the self (Stöckigt et al, 2015), and Alling provides an excellent overview including non-religious examples such as certain intense examples of conversion experiences, romantic love and encounters with nature, concluding that transcendent experiences are mystical phenomena (Alling, 2015). Surveys suggest that a third of people in the USA and the UK have had an intense religious experience like a transcendent experience that "lifted them outside of themselves" (Levin & Steele, 2005).…”
Section: Introductionmentioning
confidence: 99%